PENGARUH KAMPANYE DIGITAL TERHADAP TINGKAT KETERPILIHAN SEORANG CALON KEPALA DAERAH DALAM PEMILIHAN UMUM: Studi Eksperimen - Aliy Zayn Al'Abidiyn (2024)
In countries with democratic system, political campaigns become very fundamental and important in the political process by introducing candidates to voters. Political campaigns are now understood as planned and organized efforts that attempt to influence the reactions and understanding of voters and their choices. With the aim of winning the election, candidates are now faced with the transformation of the political process into the digital era, with how candidates must be able to plan strategies and develop their political campaigns to win votes. This article was prepared to examine the influence between the political campaign process in digital media and the succession of candidate wins and their electability. As well as identifying what factors will influence voters' beliefs, actions and perceptions of their chosen candidate. By explaining the theory and practical process, this paper concludes that the success of a candidate's campaign can be seen in how the political campaign process is planned well from digital and non-digital processes and requires strategy, tactics and a good team to maximize campaigns in this era. The regional head election contest shows the importance of adaptation and innovation in the political campaign process in the digital era. Prospective candidates who are able to understand and fully utilize the potential of digital media will have added value and competitive advantages in influencing the election process and voters and be able to win political contests. Keywords: digital media, political campaign, election